Amorphous transitional metal borides as substitutes for Pt cocatalysts for photocatalytic water splitting. (September 2016) - Li, Lihua; Deng, Zexiang; Yu, Lili; Lin, Zhaoyong; Wang, Weiliang; Yang, Guowei
Abstract: Cocatalysts for H2 production are often made from noble metals, which are expensive and rare. Cocatalysts made from cheap and abundant elements are therefore highly desirable for economically viable H2 production. Here, we demonstrate that amorphous transitional metal borides (TMBs)—made from abundant materials and costing less than 0.1% of the price of Pt cocatalysts—are effective substitutes for Pt-based cocatalysts and result in superior H2 production via water-splitting under visible light irradiation. Under visible-light driven photocatalytic water-splitting, using TMBs as cocatalysts for nanostructured NiCoB/CdS composites achieved an extraordinary H2 production of 144.8 mmol h −1  g −1, up to 36 times greater than that observed when using CdS alone. The apparent quantum efficiency was measured as 97.42% at 500 nm, which is the highest value reported for CdS photocatalysts. The hydrogen atom adsorption energy (ΔE(H)) and hydrogen molecule adsorption energy (ΔE(H2 )) of NiB, NiCoB and Pt have been calculated for the first time. Compared with Pt cocatalyst, amorphous TMBs cocatalysts more readily adsorb hydrogen protons and desorb molecular hydrogen during the photocatalytic process. Superior performance of TMBs as cocatalyst, much better than Pt, can be attributed to its powerful trapping electrons ability and highly adsorption of protons. These findings provide a straightforward and effective route to produce cheap and efficient cocatalysts for large-scale water splitting. Graphical abstract: Highlights: We, for the first time, demonstrated that amorphous transitional metal borides (TMBs) are a great substitute for noble metals (Pt) as cocatalysts for superior H2 production via water splitting under visible light irradiation. . . .